2018
DOI: 10.1074/jbc.ra117.000837
|View full text |Cite
|
Sign up to set email alerts
|

Identification of substrates of the small RNA methyltransferase Hen1 in mouse spermatogonial stem cells and analysis of its methyl-transfer domain

Abstract: Small noncoding RNAs (sncRNAs) regulate many genes in eukaryotic cells. Hua enhancer 1 (Hen1) is a 2'--methyltransferase that adds a methyl group to the 2'-OH of the 3'-terminal nucleotide of sncRNAs. The types and properties of sncRNAs may vary among different species, and the domain composition, structure, and function of Hen1 proteins differ accordingly. In mammals, Hen1 specifically methylates sncRNAs called P-element-induced wimpy testis-interacting RNAs (piRNAs). However, other types of sncRNAs that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…In contrast to plants, HEN1 homologs in animals act on single-stranded RNAs such as germline piRNAs and Ago2-associated siRNAs (but not Ago1-associated miRNA) as well as tRNA-derived sncRNAs [147] to deposit a 2'-O-methyl group on their 3' termini [147,148]. Interestingly, the substrates of HEN1 are quite different between plants and other species and this was recently proposed to be due to a conserved FxPP motif that is essential for substrate recognition [147].…”
Section: Sirna/pirna/mirna 2'-o-methylation Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to plants, HEN1 homologs in animals act on single-stranded RNAs such as germline piRNAs and Ago2-associated siRNAs (but not Ago1-associated miRNA) as well as tRNA-derived sncRNAs [147] to deposit a 2'-O-methyl group on their 3' termini [147,148]. Interestingly, the substrates of HEN1 are quite different between plants and other species and this was recently proposed to be due to a conserved FxPP motif that is essential for substrate recognition [147].…”
Section: Sirna/pirna/mirna 2'-o-methylation Enzymesmentioning
confidence: 99%
“…In Arabidopsis, 2'-O-methylation at the 3'-end of RNA is performed by the RNA methyltransferase Hua Enhancer 1 (HEN1), which methylates both miRNA/miRNA and siRNA/siRNA duplexes with a preference for 21-24 nt RNA duplexes with a 2 nt overhangs [145,146]. In contrast to plants, HEN1 homologs in animals act on single-stranded RNAs such as germline piRNAs and Ago2-associated siRNAs (but not Ago1-associated miRNA) as well as tRNA-derived sncRNAs [147] to deposit a 2'-O-methyl group on their 3' termini [147,148]. Interestingly, the substrates of HEN1 are quite different between plants and other species and this was recently proposed to be due to a conserved FxPP motif that is essential for substrate recognition [147].…”
Section: Sirna/pirna/mirna 2'-o-methylation Enzymesmentioning
confidence: 99%
“…The AtHEN1 and MpHEN1 contain two dsRBD domains that can specifically bind to an miRNA/miRNA* or siRNAs duplex but not single-stranded miRNAs or siRNAs. In contrast to plants, the HEN1 orthologs in animals can act on piRNAs or single-stranded siRNAs [40]. Moreover, not all small RNAs in animals are methylated by HEN1 orthologs.…”
Section: Hen1 Biology In Plantamentioning
confidence: 97%
“…The alignment data indicated that some SAM-binding residues and metal-binding residues were highly conserved in the MTase domain (Figure 9). The FXPP motif in the N terminus of the MTase domain is essential for substrate recognition of eukaryotic HEN1 [40]. The alignment demonstrated that plant HEN1s displayed an FXP(P/S/C) sequence in the corresponding position (Figure 9).…”
Section: Conservation Of Hen1 Orthologs In Plant Speciesmentioning
confidence: 99%
“…The exonuclease trims the 3 -end of piRNA intermediates to their mature length (Ding et al, 2017;Zhang et al, 2017b;Bronkhorst and Ketting, 2018;Nishimura et al, 2018). The 3 -end of mature piRNA is 2 -O-methylated by HENMT1, yet correct 3 truncation is not necessary for 3 -end 2 -O-methylation (Yang et al, 2006;Zhai and Meyers, 2012;Peng et al, 2018). In addition, TUT4/7 mediates the 3 uridylation of 30-to 31-nt-long piRNAs, but its effect is unknown (Morgan et al, 2019).…”
Section: Primary Pirna Biogenesismentioning
confidence: 99%